Pille Macht Diskurs Hormonelle Kontrazeption im (post-)fordistischen Sexualitätsdispositiv - Hartmann, Kris Vera (Verlag Barbara Budrich, 2021)
How has the contraceptive pill developed in Germany from a politicized to a normalized technology? The author examines a wide range of historical discourses on the pill in the FRG from 1958 to 1989 and analyzes how the pill, as a material objectivation, helped shape social power relations, standardization efforts, and ideas of emancipation.